TESIS DOCTORALES Doctoral dissertations - Hernández Esteve, Esteban (De Computis, Revista Española de Historia de la Contabilidad., 2005)
TESIS DOCTORALES Doctoral dissertations María Soledad Campos Lucena: El control de las arcas municipales a través de la rendición de cuentas. La transformación del proceso del Antiguo al Nuevo régimen y la consolidación del modelo liberal: 1745-1914 The control of municipal coffers by means of account rendering. The change from Ancien Régime to the New Regime and the consolidation of liberalism: 1745-1914 Candelaria Castro Pérez: La institución parroquial a través de los registros contables del Señorío episcopal de la Villa de Agüimes. (1500-1860) The parochial institution seen through the account books of the Episcopal domain of the city of Aguimes (1500-1860) José Julián Hernández Borreguero: El Cabildo Catedral de Sevilla: organización y sistema contable. (1625-1650) Administrative and accounting organization of the Seville Cathedral. (1625-1650) Juan Lanero Fernández: El esplendor de la teneduría de libros: la partida doble en los tratados contables ingleses de la dinastia Tudor (1543-1588) Bookkeeping splendor: double-entry in the English accounting treatises at the time of the Tudor dynasty (1543-1588) María Llompart Bibiloni: Un análisis histórico-contable de la Procuración del Real Patrimonio en el Reino de Mallorca, período 1310-1330 An accounting historical análisis of the Royal Exchequer of the Kingdom of Mallorca (1310-1330)